Румынский фактор в партизанском движении Крыма - Поляков, В.Е. (Культура народов Причерноморья, 2013)
Оккупация Крыма именно румынскими войсками стала полной неожиданностью для
организаторов партизанского движения. Отношения населения и оккупантов были сложные. Режим
оккупации способствовал восстановлению целой сети православных храмов. В составе партизан
сражались отдельные представители румынской армии. Окупація Криму саме румунськими військами стала повною несподіванкою для організаторів
партизанського руху. Відносини населення і окупантів були складні. Режим окупації сприяв відновленню
цілої мережі православних храмів. У складі партизан билися окремі представники румунської армії.
Ключові слова: Крим, румуни, партизани, перебіжчики, окупація. The occupation of the Crimea Romanian troops was a complete surprise to the organizers of the
partisan movement. This possibility was not considered entirely as a result in the units did not have translators
to conduct counter-propaganda was not procured the appropriate font. The relationship of the population and
the number of occupants of the Romanian troops were difficult.
In mid-October 1941 of the 3rd Romanian Army came to the Crimea, and on October 31 the Romanian 1st
Mountain Division on the boats crossed to the south bank of the Sivash. Official information about the beginning
of the Crimean guerrillas fighting refers to November 4, 1941. From that date to begin writing in the Journal of
the Crimean war headquarters of the partisan movement. According to the report the commander of the 4th
guerrilla zone IV Bortnikova group Eupatorium squad ambush killed one officer and four motorcyclists.In the
initial period of clashes between the guerrillas and the occupiers have occurred spontaneously. The success was
on the side of the enemy who will notice first. Not knowing about the guerrillas, the Romanian soldiers and
officers acted carelessly in the woods. On the one hand the occupation regime contributed to the restoration of a
network of Orthodox churches on the peninsula, on the other hand the population is constantly conflicts with
Romanian soldiers because of the numerous cases of looting and theft. The morale of the Romanian soldiers in
the Crimea, especially in 1943 was very low, which resulted in numerous cases of transfer of Romanian soldiers
to the guerrillas.